Immune profiling of human vestibular schwannoma secretions identifies TNF-α and TWEAK as cytokines with synergistic potential to impair hearing - Sasa Vasilijic; Richard Seist; Zhenzhen Yin; Lei Xu; Konstantina M. Stankovic (Journal of Neuroinflammation)
Abstract Background Vestibular schwannoma (VS) is an intracranial tumor arising from the Schwann cells of the vestibular nerve and is an important cause of sensorineural hearing loss (SNHL) in humans. The mechanisms underlying this SNHL are incompletely understood and currently, there are no drugs FDA approved specifically for VS. This knowledge gap significantly limits the development of effective treatments aimed at preventing, stabilizing, or reversing VS-induced SNHL. Methods To identify effector molecules involved in VS-induced SNHL, we analyzed 47 immune-related factors secreted by tumor tissue in over 50 patients with sporadic VS and studied their correlation with preoperative hearing ability and tumor size. The most promising effector molecules were validated in vivo in an anatomically accurate mouse model of VS, and in vitro with mouse fibroblasts (L929) and auditory cell lines representing pro-sensory precursors of hair cells (UB-OC1) and auditory neuroblasts (US-VOT-N33). Results We demonstrated that VS-induced SNHL was linked to increased secretion of TNF-α, IL-2R, CD163, eotaxin, and HGF, while larger tumor size was associated with higher levels of TNF-α, TNF-R2, IL-1α, IFN-α, MIP-1β, and IL-21 secretion. We identified heterogeneity among VS tumors in their capacity to secrete TNF-α. Tumors with high levels of TNF-α secretion released cytokines and chemokines that significantly correlated with poor hearing (TWEAK and eotaxin) or better hearing (LIF, GRO-α, MIP-1α, MIP-3α, and IL-1α). Among these, TWEAK was notably abundant, with levels exceeding those in normal nerve tissue, elevated in patients with non-serviceable hearing and strongly linked to poor hearing in patients with TNF-α high-secreting tumors. In vivo, we demonstrated that VS-secreted factors reach the inner ear, with elevated TNF-α and TWEAK in the perilymph and blood of tumor-bearing mice with impaired hearing. In vitro, TWEAK amplified TNF-α -mediated cytotoxicity in TNF-α sensitive cells (L929) and auditory cell lines (UB-OC1 and US-VOT-N33) at tumor-secreted concentrations. Conclusion This study provides compelling evidence that VS-secreted TNF-α and TWEAK act synergistically to drive tumor-induced SNHL. Targeting the TNF-α/TWEAK axis presents a promising new avenue for preventing VS-induced SNHL.